Short-term modern life-like stress exacerbates Aβ-pathology and synapse loss in 3xTg-AD mice - Baglietto-Vargas, David; Chen, Yuncai; Suh, Dongjin; Ager, Rahasson; Rodriguez-Ortiz, Carlos; Medeiros, Rodrigo; Myczek, Kristoffer; Green, Kim N; Baram, Tallie; LaFerla, Frank; Baglietto-Vargas, David (Wiley, 2015)
Alzheimer's disease (AD) is a progressive neurological disorder that impairs memory and other cognitive functions in the elderly. The social and financial impacts of AD are overwhelming and are escalating exponentially as a result of population aging. Therefore, identifying AD-related risk factors and the development of more efficacious therapeutic approaches are critical to cure this neurological disorder. Current epidemiological evidence indicates that life experiences, including chronic stress, are a risk for AD. However, it is unknown if short-term stress, lasting for hours, influences the onset or progression of AD. Here, we determined the effect of short-term, multi-modal ‘modern life-like’ stress on AD pathogenesis and synaptic plasticity in mice bearing three AD mutations (the 3xTg-AD mouse model). We found that combined emotional and physical stress lasting 5 h severely impaired memory in wild-type mice and tended to impact it in already low-performing 3xTg-AD mice. This stress reduced the number of synapse-bearing dendritic spines in 3xTg-AD mice and increased Aβ levels by augmenting AβPP processing. Thus, short-term stress simulating modern-life conditions may exacerbate cognitive deficits in preclinical AD by accelerating amyloid pathology and reducing synapse numbers.
Keywords: Alzheimer, Enfermedad de; Alzheimer's disease; Amyloid; Dementia; Dendritic spines; Hippocampus; Stress